2022
DOI: 10.1186/s12865-022-00476-6
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 and SPI1, may lead to the immune system dysregulation and heterotopic ossification in ankylosing spondylitis

Abstract: Objective This study was aimed to identify the biomarkers for diagnosis and reveal the immune microenvironment changes in ankylosing spondylitis (AS). Methods GSE73754 was downloaded for the co-expression network construction and immune cell analyses. Flow cytometric analysis was performed to validate the results of bioinformatics analysis. Gene set enrichment analysis (GSEA) was performed to investigate the potential biological characteristic betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In addition, activation of the IL-10/ STAT3 signaling pathway promotes macrophage polarization to the M2 type [78]. STAT3 and SPI1 are overexpressed in patients with ankylosing spondylitis and are closely associated with immune system disorders [79]. Similarly, we found that STAT3 and SPI1 were overexpressed in patients with both AMI and UC, thus suggesting that SPI1/STAT3 may be an important pathway leading to AMI and UC; however, further experimental verification is warranted.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, activation of the IL-10/ STAT3 signaling pathway promotes macrophage polarization to the M2 type [78]. STAT3 and SPI1 are overexpressed in patients with ankylosing spondylitis and are closely associated with immune system disorders [79]. Similarly, we found that STAT3 and SPI1 were overexpressed in patients with both AMI and UC, thus suggesting that SPI1/STAT3 may be an important pathway leading to AMI and UC; however, further experimental verification is warranted.…”
Section: Discussionmentioning
confidence: 61%
“…For example, PU.1 can facilitate the progression of rheumatoid arthritis by broblast-like synoviocytes and inhibiting macrophages [42] and promotes the expression of pro-in ammatory cytokines by inhibiting miR-150 in autoimmune encephalitis macrophages [43]. Over and above the previously mentioned important role of SPI1 in osteoblast differentiation and function reported by Liang et al [35], It has been reported that SPI1 can regulate the differentiation of dental pulp stem cells by inhibiting the expression of noggin [44]. This may explain the occurrence of ectopic ossi cation of AS, which in turn leads to spinal fusion.…”
Section: Discussionmentioning
confidence: 84%
“…[6,34]. Recently, Liang et al [35] found that Osteoblast differentiation and bone formation in AS may be regulated by STAT3 and SPI1 through MAPK signaling pathway, JAK/STAT and Wnt receptors, and interestingly, GSEA results showed that DYSF is highly enriched in MAPK signaling pathway, and the strong correlation between STAT3 and DYSF suggests that DYSF in AS in ammatory response may likewise play an important role. The SPI1 gene encoding PU.1 has been shown to affect the differentiation and function of multiple myeloid cells [36][37][38][39], It plays a key role in the human immune system and has been shown to be involved in the pathogenesis of many immune-related tumor diseases [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is involved in the regulation of Th17 cell development and thus in activation of the IL-23/IL-17 axis and contributes to the development of several inflammatory diseases [ 38 , 39 ]. It has recently been reported that STAT3 and SPI1 may be involved in osteoblast differentiation and bone formation in AS patients through the MAPK signalling pathway, JAK/STAT and Wnt receptors [ 40 ]. The GSEA results showed that the DYSF gene was enriched in the MAPK signalling pathway, suggesting that DYSF may be involved in osteoblast differentiation and bone formation in AS.…”
Section: Discussionmentioning
confidence: 99%